PENGARUH PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM TERHADAP BELANJA MODAL DI PROVINSI SUMATERA SELATAN - Utami, Meli; Maria Bramana, Sally (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study is entitled the influence of Local Original Income and General Allocation Funds on Capital Expenditures at the BPS of OKU Regency. The purpose of this study is to determine how much influence Local Original Income and General Allocation Funds have on Capital Expenditures at the BPS of OKU Regency.Based on the results of the analysis, the multiple linear regression equation Y = 27658.230 + 0.506 X1 - 0.020 X2 was obtained. The correlation value (R) is 0.728. This value indicates that the relationship between the independent variables, namely Regional Original Income (PAD) (X1) and the General Allocation Fund variable ( with the dependent variable, namely Capital Expenditure (Y) on Employees at the OKU Regency BPS is strong. The coefficient of determination (R Square) value is 0.530 or 53%. This value indicates the contribution of the influence of the independent variables, namely Regional Original Income (PAD) (X1) and the General Allocation Fund variable (simultaneously is 53%, the remaining 47% is the contribution of the influence of other factors not examined in this study. The t-count value of the Regional Original Income (PAD) variable (X1) is 8.108 with a t-table of 1.99085. So Ha is accepted, meaning that Regional Original Income (PAD) has a positive and significant effect on Capital Expenditure at the BPS of OKU Regency. Because tcount is greater than ttable, namely 8.108> 1.99085. The t-count value of the General Allocation Fund (X2) variable is -0.288 with a t-table of 1.99085. So Ha is rejected, meaning that the General Allocation Fund does not have a positive and significant effect on Capital Expenditure at the BPS of OKU Regency. Based on the results of the analysis, the Fcount value is 46.243. This means that Fcount> Ftable, so Ha is accepted, meaning that Regional Original Income (PAD) and General Allocation Fund have a positive and significant effect on Capital Expenditure at the BPS of OKU Regency.